Numerical investigation of heat transfer enhancement in solar air heaters using polygonal-shaped ribs and grooves - Kumar, B. Varun; Selvan, Chithirai Pon; Kanna, P. Rajesh; Taler, Dawid; Szymkiewicz, Magdalena; Taler, Jan (Frontiers in Energy Research, 2023)
Solar air heating thermal systems have found extensive utilization in a broad array of industrial and residential settings, playing a pivotal role in the conversion and reclamation of solar energy. Implementing repeated artificial roughness in the surfaces has the potential to augment thermal performance in solar air heaters (SAH). This study presents a numerical investigation of SAH with artificial rough surfaces, consisting of polygonal-shaped ribs, and grooves located at different places inside the rectangular duct, to improve thermal efficiency. ANSYS Fluent software was employed to simulate the SAH with different relative pitch distances p = 10 mm, 20 mm, and relative rib heights e/d = 0.09 -0.045. The working fluid air flows at different Reynolds numbers (Re) ranging from 3800 to 18000. Nusselt number (Nu), friction factor (f), and thermo-hydraulic performances (THP) were considered as parameters to evaluate the performance of SAH. The RNG k-ϵ turbulent model was implemented in this simulation. The study outcomes indicate that increasing the rib height improves the heat transfer rate and nonetheless increases pressure drop while increasing the pitch distance. The higher Nusselt Number (Nu) is 3.762 attained at p = 10 mm and 3.420 at p = 20 mm in the center positioned rib at (Re) 3800. The lower friction factor (ƒ) obtained in p=20 mm is 1.681 and 0.785 in p =10 mm in staggered positioned rib at higher (Re) 15000. The optimal thermo-hydraulic performance (THP) was achieved at 2.813 at a staggered rib height at a pitch distance of p = 10 mm at a (Re) 8000. The study's findings suggest that the incorporation of artificial rough surfaces has the potential to enhance the THP of a SAH.